2006
DOI: 10.1203/01.pdr.0000190576.08501.df
|View full text |Cite
|
Sign up to set email alerts
|

Association of Birth Weight with Cardiovascular Parameters in Adult Rats During Baseline and Stressed Conditions

Abstract: Low birth weight (LBW) due to intrauterine growth restriction (IUGR) in humans is associated with increased blood pressure (BP) in adulthood. In Western countries, IUGR is based on uteroplacental dysfunction. We used an animal model of uteroplacental dysfunction to evaluate this correlation. We hypothesize that IUGR increases baseline BP and alters the BP response to acute stress, which may explain BP differences in previous studies using stressful methods to obtain BP. IUGR was induced by bilateral uterine ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
1
26
2
Order By: Relevance
“…Because the glomerular volume is related to glomerular number, which is associated with birth weight, there is an indirect link between birth weight and proteinuria. Nephron endowment and raised BP in adult life have been linked (14), and we have shown a rise in systolic BP in the described model of IUGR (43).…”
Section: Discussionmentioning
confidence: 56%
“…Because the glomerular volume is related to glomerular number, which is associated with birth weight, there is an indirect link between birth weight and proteinuria. Nephron endowment and raised BP in adult life have been linked (14), and we have shown a rise in systolic BP in the described model of IUGR (43).…”
Section: Discussionmentioning
confidence: 56%
“…Tonkiss et al 26 observed an increased blood pressure response to stress in IUGR rats and suggested that the large and frequently positive findings obtained with tail cuff measurements could, to some extent, reflect an effect of programming to increase the blood pressure response to stress. A tendency toward an increased blood pressure response to stress was also apparent in 1 other study of IUGR rats 27 but absent in another. 25 Although we did not observe any effect of maternal eNOS genotype on the blood pressure response to handling and disturbance, we did observe an effect of maternal eNOS genotype on other aspects of behavior.…”
Section: Van Vliet and Chafementioning
confidence: 66%
“…Maternal eNOS Genotype Affects Offspring BPrestriction during pregnancy 26 ; an 8-, 6-, and 4-mm Hg increase in nocturnal systolic, mean, and pulse pressures, respectively, in a model of bilateral uterine artery ligation 27 ; and Յ10-and 14-mm Hg increases in diastolic and systolic pressures in offspring of mothers fed a high-fat diet during pregnancy 28,29 ). The available data suggest that, when telemetry methods are used to minimize potential stress-induced artifacts, IUGR is associated with a statistically significant though modest impact on offspring blood pressure.…”
Section: Van Vliet and Chafementioning
confidence: 99%
“…This is of interest since it contrasts with the effect of intrauterine growth retardation induced by uterine artery ligation 4 days before term (22) and may be indicative that blood pressure remains lower in the longer term in NR offspring. One alternative explanation is that they are developing a gradual rise in blood volume, thereby promoting peripheral vasodilatation.…”
Section: Discussionmentioning
confidence: 99%